Liberty Rates and Tank Mixes with Balance Flexx, Capreno, Diflexx, Halex GT, and Laudis for Weed Control in Irrigated Liberty-Resistant Corn - R. S. Currie; P. W. Geier (Kansas Agricultural Experiment Station Research Reports, 2018)
Control of common sunflower, quinoa, green foxtail, and kochia was excellent regardless of herbicide treatment or evaluation date. Palmer amaranth and crabgrass control was 95% or more regardless of herbicide treatment at 7 days after postemergence application (DAPT). Postemergence applications of Liberty (glufosinate) at any rate alone controlled Palmer amaranth greater than 85% 72 DAPT, whereas tank mixing any herbicide with Liberty increased control 7 to 15%. Crabgrass control was greater than 89% at 72 DAPT with all treatments except when Liberty at 22 oz/a was applied with Diflexx (dicamba). Corn yields did not differ among herbicide-treated plots, but all herbicide treatments increased yield 118 to 149 bu/a relative to the untreated controls.
Keywords: Sequential applications